Transition from institutional care to community care for residents of community care units in Greece: Construction of the notion of “asylum” in community care units - Dorothea Dorothea (Dialogues in Clinical Neuroscience & Mental Health, 2023)
The research study presented in this article (based on my PhD dissertation), aimed to explore the shifting meaning of “asylum” for people with severe mental illness (SMI), who are residents of community care units (CCUs), by comparing and contrasting participants’ experiences of CCUs with their previous lives in institutions. Currently, there is a gap in the Greek context in the field of qualitative studies exploring the issues of deinstitutionalisation and community care based on residents’ and staff members’ experiences. Semi-structured interviews were conducted with residents (N=35) and staff members (N=20) of four CCUs run by Klimaka (a non-governmental organisation) in Attica, the legal advisor of Klimaka, two mental health officers, a psychologist and a psychiatrist from Dromokaition Mental Health Hospital. Data were analysed thematically. Most residents felt that institutions provided a “temporary asylum” based on: 1) financial security; 2) stress-free daily routine; 3) segregation from the pressures of the outside world; 4) good or neutral relationships with staff; and 5) trust in their treatment. But most felt that the hospital had never become their actual home. All residents felt that CCUs offered them a temporary or permanent asylum, based on: 1) financial security; 2) enriched daily routine; 3) wider social networks; 4) an increased degree of freedom; 5) good relationships with staff; 6) trust in treatment, with increased awareness; and 7) absence of abuse. Twelve residents felt that the CCU was their permanent residence, while for seven of them it was a temporary one, before moving to more autonomous living conditions. The study concludes that “Asylum” does not represent a physical entity, but a set of interrelated criteria which, if met by services, can be achieved for people with SMI anywhere.